Effectiveness of ULTT and Kinesiotaping in Managing Carpal Tunnel Syndrome: A Case Study - Mardhiyyah, Shoffiyatul; Adila, Shofi; Tirta, Siti Sardianti Dwi (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/mifi.2025.v13.i02.p17, 2025)
Introduction : This case report aims to evaluate the effectiveness of combining the Upper Limb Tension Test (ULTT) and Kinesiotaping in reducing pain in a patient with Carpal Tunnel Syndrome (CTS), a neuropathy caused by compression of the median nerve, leading to pain, tingling, and hand weakness. While ULTT and Kinesiotaping have individually demonstrated benefits, their combined application is rarely explored. ULTT promotes neural mobility and facilitates nerve regeneration, potentially reducing pain. Kinesiotaping provides structural support, enhances circulation, and relieves soft tissue stress. Methods : This case study involved a 19-year-old female physiotherapy student diagnosed with CTS. The intervention included ULTT exercises and Kinesiotaping applied to the affected wrist. Pain intensity was assessed using the Visual Analog Scale (VAS), a 10 cm line ranging from “no pain” to “worst pain imaginable.” VAS scores were recorded before and after the intervention to evaluate treatment outcomes. Results : The patient reported a significant decrease in pain intensity following the combined intervention. Additionally, improvements in hand mobility and functional use were observed. Conclusion : The combination of ULTT and Kinesiotaping proved effective in reducing pain and improving hand function in a CTS patient. This approach may reduce median nerve compression, improve soft tissue function, and support neuromuscular performance. A tailored, multimodal physiotherapy strategy may enhance outcomes in CTS management, especially in younger individuals. Keywords : ULTT, Carpal Tunnel Syndrome, Kinesiotaping, Neuropathy